An Optimization Model for Transport-Storage Logistics "An Applied Study" - Mohamed Mohamed Mohamed Faragallah (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ, 2017)
This study is concerned with improving the integrated logistic problem of transport-storage in economic institutions. It provides general proposals to support designers in constructing models and developing computer software to generate optimal logistic decisions. So, closed queueing network and accompanying algorithms were proposed in modeling such problem and developing the computer software which works to perform algorithms in iterative form. It creates plans and studies the impact of them on system’s performance indicators. Thereafter, it gradually optimizes plans in each iteration until reaching the acceptable indicators. Accordingly, Port-Said cargo and container handling company (PSCCHC) was selected as an experimental case where facilities’ abilities and working limitations were studied for gaining three benefits (a) achieving fair workload distribution among quay cranes, (b) maximizing the demand time on yard cranes and (c) determining the lowest numbers of tractors that can support the previous goals. Results proved the efficiency of the proposed system.